Effects of solvent additive on “s-shaped” curves in solution-processed small molecule solar cells - Love, John A.; Chou, Shu-Hua; Huang, Ye; Bazan, Guilllermo C.; Nguyen, Thuc-Quyen (Beilstein Journal of Organic Chemistry, 2016)
A novel molecular chromophore, p-SIDT(FBTThCA8)2, is introduced as an electron-donor material for bulk heterojunction (BHJ) solar cells with broad absorption and near ideal energy levels for the use in combination with common acceptor materials. It is found that films cast from chlorobenzene yield devices with strongly s-shaped current–voltage curves, drastically limiting performance. We find that addition of the common solvent additive diiodooctane, in addition to facilitating crystallization, leads to improved vertical phase separation. This yields much better performing devices, with improved curve shape, demonstrating the importance of morphology control in BHJ devices and improving the understanding of the role of solvent additives.
Keywords: current voltage analysis; morphology; organic solar cells

(untitled) - Dou, L.; You, J.; Hong, Z.; Xu, Z.; Li, G.; Street, R. A.; Yang, Y. (Adv. Mater., 2013)

(untitled) - Liu, Y.; Zhao, J.; Li, Z.; Mu, C.; Ma, W.; Hu, H.; Jiang, K.; Lin, H.; Ade, H.; Yan, H. (Nat. Commun., 2014)

(untitled) - Li, W.; Furlan, A.; Hendriks, K. H.; Wienk, M. M.; Janssen, R. A. J. (J. Am. Chem. Soc., 2013)

(untitled) - Service, R. F. (Science, 2011)

(untitled) - Walker, B.; Tomayo, A. B.; Dang, X.-D.; Zalar, P.; Seo, J. H.; Garcia, A.; Tantiwiwat, M.; Nguyen, T.-Q. (Adv. Funct. Mater., 2009)

(untitled) - Tamayo, A. B.; Dang, X.-D.; Walker, B.; Seo, J.; Kent, T.; Nguyen, T.-Q. (Appl. Phys. Lett., 2009)

(untitled) - Henson, Z. B.; Welch, G. C.; van der Poll, T.; Bazan, G. C. (J. Am. Chem. Soc., 2012)

(untitled) - Coughlin, J. E.; Henson, Z. B.; Welch, G. C.; Bazan, G. C. (Acc. Chem. Res., 2014)

(untitled) - Wang, J.-L.; Wu, Z.; Miao, J.-S.; Liu, K.-K.; Chang, Z.-F.; Zhang, R.-B.; Wu, H.-B.; Cao, Y. (Chem. Mater., 2015)

(untitled) - Gao, K.; Li, L.; Lai, T.; Xiao, L.; Huang, Y.; Huang, F.; Peng, J.; Cao, Y.; Liu, F.; Russell, T. P.; Janssen, R. A. J.; Peng, X. (J. Am. Chem. Soc., 2015)

(untitled) - Wang, J.-L.; Xiao, F.; Yan, J.; Wu, Z.; Liu, K.-K.; Chang, Z.-F.; Zhang, R.-B.; Chen, H.; Wu, H.-B.; Cao, Y. (Adv. Funct. Mater., 2016)

(untitled) - Welch, G. C.; Perez, L. A.; Hoven, C. V.; Zhang, Y.; Dang, X.-D.; Sharenko, A.; Toney, M. F.; Kramer, E. J.; Nguyen, T.-Q.; Bazan, G. C. (J. Mater. Chem., 2011)

(untitled) - Gupta, V.; Kyaw, A. K. K.; Wang, D. H.; Chand, S.; Bazan, G. C.; Heeger, A. J. (Sci. Rep., 2013)

(untitled) - Scharber, M. C.; Mühlbacher, D.; Koppe, M.; Denk, P.; Waldauf, C.; Heeger, A. J.; Brabec, C. J. (Adv. Mater., 2006)

(untitled) - Liu, Y.; Wan, X.; Wang, F.; Zhou, J.; Long, G.; Tian, J.; Chen, Y. (Adv. Mater., 2011)

(untitled) - Li, Z.; He, G.; Wan, X.; Liu, Y.; Zhou, J.; Long, G.; Zuo, Y.; Zhang, M.; Chen, Y. (Adv. Energy Mater., 2012)

(untitled) - Liu, Y.; Wan, X.; Yin, B.; Zhou, J.; Long, G.; Yin, S.; Chen, Y. (J. Mater. Chem., 2010)

(untitled) - He, G.; Li, Z.; Wan, X.; Liu, Y.; Zhou, J.; Long, G.; Zhang, M.; Chen, Y. (J. Mater. Chem., 2012)

(untitled) - He, G.; Li, Z.; Wan, X.; Zhou, J.; Long, G.; Zhang, S.; Zhang, M.; Chen, Y. (J. Mater. Chem. A, 2013)

(untitled) - Ashraf, R. S.; Schroeder, B. C.; Bronstein, H. A.; Huang, Z.; Thomas, S.; Kline, R. J.; Brabec, C. J.; Rannou, P.; Anthopoulos, T. D.; Durrant, J. R.; McCulloch, I. (Adv. Mater., 2013)

(untitled) - McCulloch, I.; Ashraf, R. S.; Biniek, L.; Bronstein, H.; Combe, C.; Donaghey, J. E.; James, D. I.; Nielsen, C. B.; Schroeder, B. C.; Zhang, W. (Acc. Chem. Res., 2012)

(untitled) - Wang, J.-Y.; Hau, S. K.; Yip, H.-L.; Davies, J. A.; Chen, K.-S.; Zhang, Y.; Sun, Y.; Jen, A. K.-Y. (Chem. Mater., 2011)

(untitled) - Wagenpfahl, A.; Rauh, D.; Binder, M.; Deibel, C.; Dyakonov, V. (Phys. Rev. B, 2010)

(untitled) - Tress, W.; Petrich, A.; Hummert, M.; Hein, M.; Leo, K.; Riede, M. (Appl. Phys. Lett., 2011)

(untitled) - Tress, W.; Leo, K.; Riede, M. (Adv. Funct. Mater., 2011)

(untitled) - Wang, J. C.; Ren, X. C.; Shi, S. Q.; Leung, C. W.; Chan, P. K. L. (Org. Electron., 2011)

(untitled) - Finck, B. Y.; Schwartz, B. J. (Appl. Phys. Lett., 2013)

Springer Series in Materials Science - Tress, W. (Organic Solar Cells, 2014)

(untitled) - Sandberg, O. J.; Nyman, M.; Österbacka, R. (Phys. Rev. Appl., 2014)

Springer Series in Materials Science - Tress, W. (Organic Solar Cells, 2014)

(untitled) - Patra, D.; Huang, T.-Y.; Chiang, C.-C.; Maturana, R. O. V.; Pao, C.-W.; Ho, K.-C.; Wei, K.-H.; Chu, C.-W. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Zhou, J.; Wan, X.; Liu, Y.; Zuo, Y.; Li, Z.; He, G.; Long, G.; Ni, W.; Li, C.; Su, X.; Chen, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Cui, C.; Min, J.; Ho, C.-L.; Ameri, T.; Yang, P.; Zhao, J.; Brabec, C. J.; Wong, W.-Y. (Chem. Commun., 2013)

(untitled) - Patra, D.; Chiang, C.-C.; Chen, W.-A.; Wei, K.-H.; Wu, M.-C.; Chu, C.-W. (J. Mater. Chem. A, 2013)

(untitled) - Zhou, J.; Wan, X.; Liu, Y.; Long, G.; Wang, F.; Li, Z.; Zuo, Y.; Li, C.; Chen, Y. (Chem. Mater., 2011)

(untitled) - Benaglia, M.; Toyota, S.; Woods, C. R.; Siegel, J. S. (Tetrahedron Lett., 1997)

(untitled) - Liu, X.; Sun, Y.; Hsu, B. B. Y.; Lorbach, A.; Qi, L.; Heeger, A. J.; Bazan, G. C. (J. Am. Chem. Soc., 2014)

(untitled) - Sun, Y.; Welch, G. C.; Leong, W. L.; Takacs, C. J.; Bazan, G. C.; Heeger, A. J. (Nat. Mater., 2012)

(untitled) - van der Poll, T. S.; Love, J. A.; Nguyen, T.-Q.; Bazan, G. C. (Adv. Mater., 2012)

(untitled) - Love, J. A.; Nagao, I.; Huang, Y.; Kuik, M.; Gupta, V.; Takacs, C. J.; Coughlin, J. E.; Qi, L.; van der Poll, T. S.; Kramer, E. J.; Heeger, A. J.; Nguyen, T.-Q.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Takacs, C. J.; Sun, Y.; Welch, G. C.; Perez, L. A.; Liu, X.; Wen, W.; Bazan, G. C.; Heeger, A. J. (J. Am. Chem. Soc., 2012)

(untitled) - Love, J. A.; Proctor, C. M.; Liu, J.; Takacs, C. J.; Sharenko, A.; van der Poll, T. S.; Heeger, A. J.; Bazan, G. C.; Nguyen, T.-Q. (Adv. Funct. Mater., 2013)

(untitled) - Love, J. A.; Collins, S. D.; Nagao, I.; Mukherjee, S.; Ade, H.; Bazan, G. C.; Nguyen, T.-Q. (Adv. Mater., 2014)

(untitled) - Amb, C. M.; Chen, S.; Graham, K. R.; Subbiah, J.; Small, C. E.; So, F.; Reynolds, J. R. (J. Am. Chem. Soc., 2011)

(untitled) - Koster, L. J. A.; Mihailetchi, V. D.; Ramaker, R.; Blom, P. W. M. (Appl. Phys. Lett., 2005)

(untitled) - Mihailetchi, V. D.; Koster, L. J. A.; Hummelen, J. C.; Blom, P. W. M. (Phys. Rev. Lett., 2004)

(untitled) - Mihailetchi, V. D.; Wildeman, J.; Blom, P. W. M. (Phys. Rev. Lett., 2005)

(untitled) - Mihailetchi, V. D.; Xie, H. X.; de Boer, B.; Koster, L. J. A.; Blom, P. W. M. (Adv. Funct. Mater., 2006)

(untitled) - Blom, P. W. M.; Mihailetchi, V. D.; Koster, L. J. A.; Markov, D. E. (Adv. Mater., 2007)

(untitled) - Andersson, L. M.; Müller, C.; Badada, B. H.; Zhang, F.; Würfel, U.; Inganäs, O. (J. Appl. Phys., 2011)

(untitled) - Albrecht, S.; Janietz, S.; Schindler, W.; Frisch, J.; Kurpiers, J.; Kniepert, J.; Inal, S.; Pingel, P.; Fostiropoulos, K.; Koch, N.; Neher, D. (J. Am. Chem. Soc., 2012)

(untitled) - Tvingstedt, K.; Vandewal, K.; Zhang, F.; Inganäs, O. (J. Phys. Chem. C, 2010)

(untitled) - Credgington, D.; Jamieson, F. C.; Walker, B.; Nguyen, T.-Q.; Durrant, J. R. (Adv. Mater., 2012)

(untitled) - Perez, L. A.; Chou, K. W.; Love, J. A.; van der Poll, T. S.; Smilgies, D.-M.; Nguyen, T.-Q.; Kramer, E. J.; Amassian, A.; Bazan, G. C. (Adv. Mater., 2013)

(untitled) - Perez, L. A.; Rogers, J. T.; Brady, M. A.; Sun, Y.; Welch, G. C.; Schmidt, K.; Toney, M. F.; Jinnai, H.; Heeger, A. J.; Chabinyc, M. L.; Bazan, G. C.; Kramer, E. J. (Chem. Mater., 2014)

(untitled) - McDowell, C.; Abdelsamie, M.; Zhao, K.; Smilgies, D.-M.; Bazan, G. C.; Amassian, A. (Adv. Energy Mater., 2015)

(untitled) - Proctor, C. M.; Love, J. A.; Nguyen, T.-Q. (Adv. Mater., 2014)

(untitled) - Zalar, P.; Kuik, M.; Ran, N. A.; Love, J. A.; Nguyen, T.-Q. (Adv. Energy Mater., 2014)

(untitled) - Mihailetchi, V. D.; Blom, P. W. M.; Hummelen, J. C.; Rispens, M. T. (J. Appl. Phys., 2003)

(untitled) - Schulze, K.; Uhrich, C.; Schüppel, R.; Leo, K.; Pfeiffer, M.; Brier, E.; Reinold, E.; Bäuerle, P. (Adv. Mater., 2006)

(untitled) - Jin, H.; Tuomikoski, M.; Hiltunen, J.; Kopola, P.; Maaninen, A.; Pino, F. (J. Phys. Chem. C, 2009)

(untitled) - Nelson, J.; Kirkpatrick, J.; Ravirajan, P. (Phys. Rev. B, 2004)

(untitled) - Tan, Z.-K.; Vaynzof, Y.; Credgington, D.; Li, C.; Casford, M. T. L.; Sepe, A.; Huettner, S.; Nikolka, M.; Paulus, F.; Yang, L.; Sirringhaus, H.; Greenham, N. C.; et al. (Adv. Funct. Mater., 2014)

(untitled) - Deibel, C.; Dyakonov, V. (Rep. Prog. Phys., 2010)

(untitled) - Magee, C. W. (Ultramicroscopy, 1984)

(untitled) - Treat, N. D.; Brady, M. A.; Smith, G.; Toney, M. F.; Kramer, E. J.; Hawker, C. J.; Chabinyc, M. L. (Adv. Energy Mater., 2011)

(untitled) - van Duren, J. K. J.; Yang, X.; Loos, J.; Bulle-Lieuwma, C. W. T.; Sieval, A. B.; Hummelen, J. C.; Janssen, R. A. J. (Adv. Funct. Mater., 2004)

(untitled) - Subbiah, J.; Amb, C. M.; Reynolds, J. R.; So, F. (Sol. Energy Mater. Sol. Cells, 2012)

(untitled) - Sun, Y.; Seo, J. H.; Takacs, C. J.; Seifter, J.; Heeger, A. J. (Adv. Mater., 2011)

(untitled) - Zhou, Y.; Fuentes-Hernandez, C.; Shim, J.; Meyer, J.; Giordano, A. J.; Li, H.; Winget, P.; Papadopoulos, T.; Cheun, H.; Kim, J.; Fenoll, M.; Dindar, A.; et al. (Science, 2012)